Engineered Removal of PD-1 From the Surface of CD19 CAR-T Cells Results in Increased Activation and Diminished Survival - Kalinin, R. S.; Ukrainskaya, V. M.; Chumakov, S. P.; Moysenovich, A. M.; Tereshchuk, V. M.; Volkov, D. V.; Pershin, D. S.; Maksimov, E. G.; Zhang, H.; Maschan, M. A.; Rubtsov, Y. P.; Stepanov, A. V. (Frontiers in Molecular Biosciences, 2021)
CAR-T cell therapy is the most advanced way to treat therapy resistant hematologic cancers, in particular B cell lymphomas and leukemias, with high efficiency. Donor T cells equipped ex vivo with chimeric receptor recognize target tumor cells and kill them using lytic granules. CAR-T cells that recognize CD19 marker of B cells (CD19 CAR-T) are considered the gold standard of CAR-T therapy and are approved by FDA. But in some cases, CD19 CAR-T cell therapy fails due to immune suppressive microenvironment. It is shown that tumor cells upregulate expression of PD-L1 surface molecule that binds and increases level and signal provided by PD-1 receptor on the surface of therapeutic CAR-T cells. Induction of this negative signaling results in functional impairment of cytotoxic program in CAR-T cells. Multiple attempts were made to block PD-1 signaling by reducing binding or surface level of PD-1 in CAR-T cells by various means. In this study we co-expressed CD19-CAR with PD-1-specific VHH domain of anti-PD-1 nanobody to block PD-1/PD-L1 signaling in CD19 CAR-T cells. Unexpectedly, despite increased activation of CAR-T cells with low level of PD-1, these T cells had reduced survival and diminished cytotoxicity. Functional impairment caused by disrupted PD-1 signaling was accompanied by faster maturation and upregulation of exhaustion marker TIGIT in CAR-T cells. We conclude that PD-1 in addition to its direct negative effect on CAR-induced signaling is required for attenuation of strong stimulation leading to cell death and functional exhaustion. These observations suggest that PD-1 downregulation should not be considered as the way to improve the quality of therapeutic CAR-T cells.